Respostas

2013-05-06T09:51:31-03:00
 √6 (√2+√3) =

 3√5 (1-√10) =

 (√7+√3) (√7 - √3) = (OBS: entre parentese e outro na conta não tem nenhum sinal)

 (√48+√24) : √3 =

 (9 √12-8√10) : 3√2 =

 (10 √20-15 √5) : 5 √5.   como fazer:    √6 (√2+√3) = √6√2 + √6√3=√6.2 + √6.3 =2√3+3√2

 3√5 (1-√10) = 3√5 - 3√5 √10 = 3√5 - 3√5.10 = 3√5 - 3√25.2 =
3√5 -15√2
 (√7+√3) (√7 - √3) = √7² - √7√3 + √7√3 - √3² = 7 - 3 = 4 

 (√48+√24) : √3 = (√16.3 + √8.3)/√3 = (4√3 +2√3)/√3 = 4+2 = 6

 (9 √12-8√10) : 3√2 = (√81.12 - √64.10) :√18

 (10 √20-15 √5) : 5 √5 =
2 3 2